2001
DOI: 10.1159/000054062
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Aberrations in Lymphocytes of Residents Living in Buildings Constructed with Radioactively Contaminated Rebars

Abstract: Using the G-banding technique, we examined lymphocytes from 90 individuals (43 males and 47 females, median age 31 years) living in buildings constructed with radioactively contaminated rebars. Forty-five nonexposed control subjects (22 males and 23 females, median age 30 years), matched to the radiation-exposed individuals by sex and age, were selected for comparison. At least 500 metaphases were checked for each individual. All recognizable structural aberrations of chromosomes or chromatids were recorded. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…As it has been shown that radiation exposure from the Chernobyl reactor accident caused an elevated rate of chromosomal aberrations [1], Wang-Wuu et al [17] examined the effect of radiation on these residents in Taiwan. As of June I998, 1,566 families still reside in these buildings.…”
Section: Cytogenetic Effect Of Radiation Exposurementioning
confidence: 99%
“…As it has been shown that radiation exposure from the Chernobyl reactor accident caused an elevated rate of chromosomal aberrations [1], Wang-Wuu et al [17] examined the effect of radiation on these residents in Taiwan. As of June I998, 1,566 families still reside in these buildings.…”
Section: Cytogenetic Effect Of Radiation Exposurementioning
confidence: 99%